2019
DOI: 10.1136/bmjopen-2019-033246
|View full text |Cite
|
Sign up to set email alerts
|

Short-term outcomes of rapid initiation of antiretroviral therapy among HIV-positive patients: real-world experience from a single-centre retrospective cohort in Taiwan

Abstract: ObjectivesRapid initiation of antiretroviral therapy (ART) engenders faster viral suppression but with suboptimal rates of durable viral suppression and engagement in care, as reported by clinical trials in resource-limited settings. Real-world experience with rapid ART initiation remains limited in resource-rich settings.DesignRetrospective cohort study.SettingA tertiary hospital in metropolitan Taipei, Taiwan.ParticipantsWe included 631 patients newly diagnosed as having HIV infection between March 2014 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 29 publications
3
23
1
Order By: Relevance
“…But there was increasing in the proportion of newly diagnosed HIV positive people who initiated ART within 7 days of HIV diagnosis to 65.6%. The finding was in line with a study in South Africa with overall same-day ART initiation of 40.1% and initiated within 7 days to 62.86% [ 15 ] and similar with study from Taiwan reported 68% rapid ART initiation within 7 days of HIV confirmed diagnosis in 2017 [ 8 ]. However, same-day ART initiation was lower compared to the recent finding of 54.2% in June 2018 in South Africa [ 15 ], Zimbabwe (65%) [ 55 ], 94.9% in US [ 56 ] and San Francisco (96%) [ 57 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…But there was increasing in the proportion of newly diagnosed HIV positive people who initiated ART within 7 days of HIV diagnosis to 65.6%. The finding was in line with a study in South Africa with overall same-day ART initiation of 40.1% and initiated within 7 days to 62.86% [ 15 ] and similar with study from Taiwan reported 68% rapid ART initiation within 7 days of HIV confirmed diagnosis in 2017 [ 8 ]. However, same-day ART initiation was lower compared to the recent finding of 54.2% in June 2018 in South Africa [ 15 ], Zimbabwe (65%) [ 55 ], 94.9% in US [ 56 ] and San Francisco (96%) [ 57 ].…”
Section: Discussionsupporting
confidence: 91%
“…In South Africa, the same-day initiation of ART was 40.1% from 2017 to 2018 in which increased from 30.3% in October 2017 to 54.2% in June 2018 [ 15 ]. In Taiwan, rapid initiation of ART was 33.8% in 2014 and increasing to 68.3% in 2017 [ 8 ]. Similarly in San Diego, 26 and 48% of newly diagnosed HIV positive individuals started ART on the same-day of diagnosis and within a week respectively [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Being female, urban dwellers, disclosing HIV serostatus, college and above educational level, having no baseline OIs, linked from OPD and getting tested for HIV via VCT approach were the predictors of early ART initiation. The overall incidence rate of ART initiation that was revealed in this study was 51.9/1000 person-days observation in which 67.4% [95% CI: 59.3-73.5] of them initiated the ART on the same day of confirmed 34 However, this result is higher than a study result conducted in Ethiopia, 35 and South Africa, 36 which reported the rate of the same day ART initiation among newly diagnosed HIV positive people was 40.90% and 40.4%, respectively. This inconsistency might be attributable to the study period and setting difference.…”
mentioning
confidence: 58%
“…The median age of newly diagnosed HIV positive people was 35 [IQR: [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] years. The majority of the study participants (164; 31.66%) were found in age category of ≥40 years old.…”
Section: Socio-demographic Characteristics Of Study Participantsmentioning
confidence: 99%
“…Individuals seeking VCT services have been offered free-of-charge testing for HIV and syphilis. Those testing positive for HIV or syphilis are linked to medical care and receive treatment and further evaluation for viral hepatitis and other STDs [ 17 ].…”
Section: Methodsmentioning
confidence: 99%